Pengaruh Gaya Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada PT. Profilia Indotech Surabaya) - Moch Indrawan; Bambang Karnain; Achmad Daengs GS; Sugiharto Sugiharto; Diana Zuhro (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of leadership style, motivation and work discipline on the performance of PT.Profilia Indotech Surabaya employees. The type of research used is quantitative and information is collected through questionnaires. The sample in this study are employees of PT. Profilia Indotech Surabaya as many as 37 respondents. The analytical method used is descriptive analysis with SPSS 25 application tools namely validity analysis, reliability analysis, multiple linear regression analysis, multicollinearity, heteroscedasticity, normality, hypothesis testing (t test and F test) and the coefficient of determination (R2). The results show that leadership style partially has a significant influence on employee performance, with a significance value of α = 0.00 <0.05 with a tcount greater than ttable -4.368> -2.03452. Motivation partially has a significant influence on employee performance, with a significance value of α = 0.00 <0.05 with a tcount greater than ttable 23.861> 2.03452. Discipline partially has a significant influence on employee performance, with a significance value of α = 0.02 <0.05 with a tcount greater than ttable 3.378> 2.03452. And simultaneously leadership style, motivation and discipline have a significant influence on employee performance, with a significance value of α = 0.00 <0.05 with a Fcount value greater than Ftable 193.850> 2.89. From this study is that the variables of leadership style, motivation and work discipline have a significant effect on employee performance.